2023
DOI: 10.21203/rs.3.rs-2432228/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical spectrum of ear, nose and throat foreign bodies at a tertiary hospital in Zanzibar, Tanzania

Abstract: Objective: Presence of foreign bodies (FBs) in the ears and upper aerodigestive tract is a common encounter in children unlike adults in otorhinolaryngology practice. Such foreign bodies form a major part of emergencies that the otorhinolaryngologist needs to attend. The high prevalence in children can be attributable to the inquisitive nature of children and their tendency to explore the environment. This study was a cross sectional study that aimed to determine the clinical spectrum of such foreign bodies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Our study showed that there is predominance of esophageal FBs in younger children. The most frequently swallowed FBs in children is coins like many studies [13][14][15] and meat and meat bones (chicken bone/fish bone/mutton), although the latter is more common in adults. The ingestion of coins probably because young children have earlier access to coins since they help with household tasks, namely going alone to buy bread or fruit at stalls located on the side of the road.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that there is predominance of esophageal FBs in younger children. The most frequently swallowed FBs in children is coins like many studies [13][14][15] and meat and meat bones (chicken bone/fish bone/mutton), although the latter is more common in adults. The ingestion of coins probably because young children have earlier access to coins since they help with household tasks, namely going alone to buy bread or fruit at stalls located on the side of the road.…”
Section: Discussionmentioning
confidence: 99%